ChemInform Abstract: Garratt—Braverman Cyclization, a Powerful Tool for C—C Bond Formation. Issue 7 (22nd February 2013) - Mondal, Sayantan; Mitra, Tapobrata; Mukherjee, Raja; Addy, Partha Sarathi; Basak, Amit
Abstract Review: ca. 80 refs.